Islamic revival and cultural diversity: pesantren’s configuration in contemporary Aceh Indonesia - Bambang Arif Rahman (IAIN Salatiga, 2022)
This study aims at investigating the extent to which pesantren (Islamic boarding school) in Aceh, Indonesia have flourished in encountering multicultural situations in the post-disaster of a massive tsunami and post-separatist-military conflict through the lens of Islamic revivalism. A decade and a half after the gigantic natural disaster in 2004 and the protracted bloody conflict, Aceh underwent various changes in social, economic, political, educational, and religious areas. In the educational and religious sectors, a pivotal metamorphose took place in pesantren as a means of Islamic revival, where this Islamic boarding school has transformed into multicultural institutions. Using a qualitative design, this study observed a small number of pesantren in Aceh, interviewed their key stakeholders, and analyzed pesantren documents. The findings show that pesantren cultures in contemporary Aceh differ from previous monolithic traditional Islamic schools in curriculum, characteristics, typology, and affiliation. This change is a unique mark of an Islamic revival following the influx of the plural Indonesian and of the world communities to Aceh after the catastrophe and violence with their heterogeneous aids and cultural settings. In addition, the implementation of shari’a (Islamic) law in this special province after both tragedies confirmed the work of the Islamic revival, though many nationalists sharply criticize this sectarian and exclusive law within multicultural countries like Indonesia. However, in this situation, pesantren in Aceh expressed a positive commitment to celebrating cultural diversity through ethnicity respect, religious tolerance, and Indonesian unity rather than endorsing the idea of an Islamic state.